Comprehensive analysis of atherosclerotic plaques reveals crucial genes and molecular mechanisms associated with plaque progression and rupture - Zhu, Guoqi; Gao, Yanhua; Qian, Jun; Lai, Yan; Lin, Hao; Liu, Chengxing; Chen, Fei; Liu, Xuebo (Frontiers in Cardiovascular Medicine, 2023)
Background: Plaque rupture and acute atherothrombosis, resulting from continued progression of atherosclerotic plaques (APs), are major contributors to acute clinical events such as stroke or myocardial infarction (MI). This article aimed to explore the gene signatures and potential molecular mechanisms in the progression and instability of APs and to identify novel biomarkers and interventional targets for APs rupture. Methods: The microarray data were downloaded from the Gene Expression Omnibus (GEO) database and grouped into discovery and validation cohorts. In discovery cohort, Weighted Gene Co-Expression Network Analysis (WGCNA) was performed for finding co-expression modules, and the Metascape database was used to perform functional enrichment analysis. Differential Expression Genes (DEGs) analysis subsequently be performed in validation cohort for verification of the obtained results. The common genes were introduced into Metascape database for PPI and functional enrichment analysis. We constructed the miRNAs–mRNAs network with the hub genes. Moreover, gene expression profiles of PBMCs from peripheral blood of patients with plaque rupture were analyzed by high-throughput sequencing, and the diagnostic power of hub genes was verified by ROC analysis. Results: In discovery cohort, the brown module in GSE28829 and the turquoise module in GSE163154 were the most significant co-expression modules. Functional enrichment analysis of shared genes suggested that “Neutrophil degranulation” was the most significantly enriched pathway. These conclusions were also demonstrated by the validation cohort. A total of 16 hub genes were identified. The miRNA-mRNA network revealed that hsa-miR-665 and hsa-miR-512-3p might regulate the “Neutrophil degranulation” pathway through PLAU and SIRPA, which might play a significant role in APs progression and instability. Five hub genes, including PLAUR, FCER1G, PLAU, ITGB2 and SLC2A5, showed significantly increased expression in PBMCs from patients with plaque rupture compared with controls. ROC analysis finally identified three hub genes PLAUR, FCER1G and PLAU that could effectively distinguish patients with APs rupture from controls. Conclusions: The present study demonstrated that the “Neutrophil degranulation” signaling pathways and identified novel mRNA and miRNA candidates is closely associated with plaque progression and instability. The hub genes FCER1G, PLAUR and PLAU may serve as biomarkers for the prospective prediction of APs rupture.